Research on Deriving a Proportional System of a Roof Structure Through the Analysis of Hanok Architectural Design Methods - Byeong-Uk Shin (Buildings)
Hanoks are structures that have been built with unique techniques and styles since prehistoric times. Demand for hanoks is growing because they are recognized as climate-friendly buildings that make use of the natural environment as it is. However, there are a lack of standardized records concerning the methods or standards for constructing hanoks, so inferring them through the dimensional analysis of existing buildings is challenging. The roof of a hanok is its most beautiful part, and its proportions change the appearance of the hanok. Relying on existing examples or inherited figures when designing hanoks has led to the formation of uniform hanoks and the loss of their identity due to the lack of proportional standards. This study aimed to derive a proportional roof structure system by analyzing hanok architectural design methods. The employed method allowed for an analysis of the types of roofs and eaves of hanoks and extracted all the roof-related factors, such as the eave overhang, eave angle, roof angle, and hanok height. These data were compared with each other to find regularities and derive a final proportional system for a hanok roof structure. The analysis showed that the eave-height-to-roof-height ratio is 5.5:4.5, and notably, the sum of the eave and roof angles is in the range of 118°~120°, which means that the lower the eave angle, the higher the roof angle. Therefore, the roof structure of a hanok should not be designed based on a partial average value; rather, it should be based on a mutual proportional system considering the eave angle, roof angle, hanok height, and eave height. The results of this study can provide designers with a basis for creating hanoks through the use of the proportional system of roofs. This data basis guarantees continuity between the past and the present, and the proposed system can serve as a guide for hanok roof design and structural analysis.